Analyzing the Relationship between Oil Prices and Gold Prices before and after COVID-19 - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2023)
The main purpose of this study is to investigate the causal relationship between world oil prices and gold prices. For this purpose, the study is divided into two groups and evaluated as pre-pandemic and post-pandemic. The data set required for the study is evaluated on a daily basis and includes the period from January 2011 to June 2022. For the data of the examined variables, the stationary test was carried out by using the Extended DickeyFuller (ADF) unit root test. In the case of level, it is concluded that the related series are not stationary for these variables. According to the ADF and Johansen cointegration results obtained by applying the first-order difference operation, it was determined that the first-order differences of the variables of interest were stationary, that is, there was no unit root. The Engle-Granger test was used to determine whether there is a long-term relationship between the two variables. The direction of the relationship was tried to be determined by using the Granger causality test. As a result of the study, it was concluded that there is a one-way causality relationship from gold prices to oil prices, before the pandemic.